2019
DOI: 10.1002/cncr.32607
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and demographic features of neuroendocrine tumors in the United States of America: A population‐based study

Abstract: BACKGROUND: The incidence of neuroendocrine tumors (NETs) is rapidly rising. There are very few studies investigating the role of sociodemographic factors in NETs. This study was aimed at examining how geographic and sociodemographic characteristics shape outcomes in the NET population. METHODS: A retrospective analysis using the Surveillance, Epidemiology, and End Results database was performed, and the NET patient population from 1973 to 2015 was studied. Univariate and multivariable analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(64 reference statements)
3
14
0
Order By: Relevance
“…Our study is the first to demonstrate that being single, divorced, or widowed is a risk factor associated with primary site-labeled conjunctival and corneal cancer incidence. Prior studies have primarily only examined the relationship between marital status and other forms of cancer including colorectal cancer [ 22 ], neuroendocrine tumors [ 23 ], and gastric adenocarcinoma [ 24 ] in retrospective [ 25 ] analyses or in prospective analyses [ 26 ]. While several studies have assessed the relationship between marital status and patient prognosis, conclusions have varied significantly among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to demonstrate that being single, divorced, or widowed is a risk factor associated with primary site-labeled conjunctival and corneal cancer incidence. Prior studies have primarily only examined the relationship between marital status and other forms of cancer including colorectal cancer [ 22 ], neuroendocrine tumors [ 23 ], and gastric adenocarcinoma [ 24 ] in retrospective [ 25 ] analyses or in prospective analyses [ 26 ]. While several studies have assessed the relationship between marital status and patient prognosis, conclusions have varied significantly among studies.…”
Section: Discussionmentioning
confidence: 99%
“…The first was the US‐based Surveillance, Epidemiology, and End Results (SEER) Program registry analysis, including 35,618 NEN patients, that reported a significant increase in the annual age‐adjusted incidence from 1.09/100,000 in 1973 to 5.25/100,000 in 2004 6 . The most rapid increase has been in the age bracket 40–69 years, 5,11 , localized disease, primary tumoral sites especially small bowel, 8 rectum then stomach, 5,7,12 across all histological grades, 2 and in rural and urban regions 13 …”
Section: Introductionmentioning
confidence: 99%
“…As there is a significant difference in racial composition between urban and rural populations, this begs the question of the role of race in neuroendocrine cancer outcomes. 13 Although Black patients comprised 12.8% to 13.7% of patients in the database studies, 24.5% of our patients were Black due to our unique position as the sole comprehensive cancer center in a state with one of the largest African American populations. 6,11,12 In addition, although 59.0% of the Alabama state population is located in urban areas, 95.6% of the state land area is rural.…”
mentioning
confidence: 88%
“…These studies found rural patients have an increased incidence of neuroendocrine tumors with an associated decreased OS and DFS as compared with urban populations. [13][14][15] However, there were significant confounders to this geographic disparity, such as income, race, and marital status. As there is a significant difference in racial composition between urban and rural populations, this begs the question of the role of race in neuroendocrine cancer outcomes.…”
mentioning
confidence: 99%